Bentho-pelagic relations in the deep-water part of the Okhotsk Sea by the data of stable isotopes С and N analysis - Konstantin M. Gorbatenko; Sergey I. Kiyashko; Artem E. Lazhentsev; Pavel O. Emelin; Ruslan P. Grishan (Известия ТИНРО, 2015)
Composition, abundance, diet and trophic status are analyzed for dominant benthic and pelagic species in the deep-water Okhotsk Sea on the data collected in demersal and pelagic trawl surveys conducted by Pacific Fisheries Research Center (TINRO). Isotope composition of13С and15N is determined for tissues of 107 species of plankton, benthos, demersal fish, and cephalopods, which form a basis of pelagic and benthic communities. The carbon isotope content is significantly different between these groups: d13С ranges from -23.30 to -19.90 ‰ for zooplankton, from -18.90 to -13.33 ‰ for benthos, from -22.10 to -18.90 ‰ for fish (mean values), and from -20.08 to -15.75 ‰ for cephalopods. It depends mainly on proportion of pelagic and benthic food in their diet. Following to these values, 30 % of examined species of demersal fishes and cephalopods use resources of detritus food chain as the base of their diet. The range of d15N is from 6.79 ( Megayoldia thraciaeformis ), 6.88 ( Eucalanus bungii ) to 18.26 ‰ ( Molpadia roretzii ). Its highest level is observed for 4 species of benthic invertebrates and 8 species of demersal fishes on the continental slope characterized by high tropic level (≥5) and included to the bentho-pelagic food chain, that corresponds with their d13С values. Trophic relations in the deep-water Okhotsk Sea demonstrates high dependence between benthic and pelagiс communities, as far as many dominant species of pelagic and demersal nekton consume both benthic and pelagic food. Feeding about of 70 % of dominant species of demersal fishes and cephalopods is based on grazing rather than on detritus food.